Correlation between 25-Hydroxyvitamin D, sFlt-1, PLGF, and Hypertension in Pregnancy - Wei Wang (Hindawi Limited, 2021)
Gestational hypertension is a common disease in clinical practice, which does great harm to the mother and infant. The purpose of this study was to investigate the relationship between 25-hydroxyvitamin D, sFlt-1, and PLGF and hypertensive disorder complicating pregnancy. Specimen preparation: after delivery or placental caesarean section, in order to avoid calcification and necrosis in the middle of the placenta, an area of about 1.5 cm × 1.5 cm × 1.5 cm should be separated immediately. After dehydration, use a Citadel 2000 dryer to dry it and place it in a block of saline for xylene immunohistochemical staining. Statistical processing was performed according to the proportion of positive cells in each part and the depth of staining. Placental tissue collection and treatment: within 20 minutes after the delivery of the placenta, two pieces of the placental tissue (about 1.0 cm × 1.0 cm × 1.0 cm) were taken from the central zone of the placental maternal surface without obvious bleeding and calcification. They were rinsed repeatedly in normal saline, fixed in 10% neutral formaldehyde solution for 24 hours, dehydrated using an automatic dehydrator, and embedded in paraffin for detection. Before the study, 20 ml of distilled water was added to the sample to stand for 20 minutes; the Cobas E610 immunoanalyzer was turned on, and sFlt-1 and PLGF (placental growth factor) were selected. The serum 25-hydroxyvitamin D level of pregnant women was detected in the fasting state at 24–28 weeks of gestation, and the best collection time was 8 : 00–11 : 00 in the morning. 5 ml of the whole blood sample without anticoagulant was collected and stored at 0–4°C in a cold storage and dark environment. The serum was obtained by high-speed centrifugation within 24 hours after collection. The method is suitable for the quantitative determination of 25-OH-vitamin D in human serum. In the hypertensive pregnancy group, the level of 25-hydroxyvitamin D was 18.44 ± 3.48 ng/ml, and the sFlt-1/PLGF level was highest at 0–5 weeks followed by 5–10 weeks, 10–15 weeks, and 15–20 weeks. This study provides new ideas and experimental clues for the prevention and treatment of pre-eclampsia.